Mutations Associated with Rifampicin Resistance in Mycobacterium tuberculosis Isolates from Moroccan Patients: Systematic Review - Eddabra, Rkia; Neffa, Mounsef (Interdisciplinary Perspectives on Infectious Diseases, 2020)
Background. In recent years, the treatment of tuberculosis has been threatened by the increasing number of patients with drug resistance, especially rifampicin resistance, which is the most effective first-line antibiotic against Mycobacterium tuberculosis. Methods. We performed a systematic review of the literature by searching the PubMed database for studies of rifampicin-resistant Mycobacterium tuberculosis (MTB) isolates from Moroccan patients, published between 2010 and 2020. The aim of this review was to quantify the frequency of the most common mutations associated with rifampicin resistance, to describe the frequency at which these mutations co-occur. Identified studies were critically appraised according to the Quality Assessment of Diagnostic Accuracy Studies-2 (QUADAS-2) tool. Results. 6 studies met our inclusion criteria. Results show that 99.36% of MTB isolates had a single-point mutation, and the most commonly mutated codon of rpoB gene is 531 with 70.33% of phenotypically resistant strains. However, 10.38% of MTB strains phenotypically resistant to RIF did not exhibit any mutation in the rpoB gene. Conclusion. Identification of a resistance-associated mutation to rifampicin can be a good marker of drug-resistant TB, but lack of a mutation in the target sequence must be interpreted with caution.